ANALISIS PENGARUH PEMBELAJARAN TERPADU TERHADAP PRESTASI BELAJAR SISWA KELAS V SD INPRES NAIMATA KOTA KUPANG - Mbuik, Heryon Bernard; Vlora.Toineno, Dewi Banamtuan; Elisabetth Rakmeni, Tarmi Nenometa; Imanuel Bani, Yuliana Halek; Chirstoforus Ngabu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Basic education plays a strategic role as the initial foundation in forming students' identity, moral character, and literacy and numeracy skills. This study was conducted to examine whether integrated learning has an impact on the learning achievement of fifth grade students at SD Inpres Naimata, Kupang City. The research method used is descriptive quantitative, which will describe in detail all aspects that are the focus of the research. Data collection was carried out through observation, question and answer, and distributing questionnaires. From the results of the study, it was revealed that the implementation of integrated learning had a positive effect on increasing student learning achievement